2011
DOI: 10.1098/rspa.2011.0584
|View full text |Cite
|
Sign up to set email alerts
|

Non-local effects in radial heat transport in silicon thin layers and graphene sheets

Abstract: We explore non-local effects in radially symmetric heat transport in silicon thin layers and in graphene sheets. In contrast to one-dimensional perturbations, which may be well described by means of the Fourier law with a suitable effective thermal conductivity, twodimensional radial situations may exhibit a more complicated behaviour, not reducible to an effective Fourier law. In particular, a hump in the temperature profile is predicted for radial distances shorter than the mean-free path of heat carriers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Besides, the molecular dynamics [14] and MC [15] simulations were also employed to investigate the effective thermal conductivity. Sellitto et al [16] investigated the steady-state radical heat transport in silicon thin layers based on phonon hydrodynamics and found that two-dimensional radial situations cannot be reducible to Fourier law with the effective thermal conductivity. As for experiments, Liu & Asheghi [17,18] obtained the in-plane effective thermal conductivity of silicon films by introducing a steady-state uniform internal heat source and measuring the average temperature increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the molecular dynamics [14] and MC [15] simulations were also employed to investigate the effective thermal conductivity. Sellitto et al [16] investigated the steady-state radical heat transport in silicon thin layers based on phonon hydrodynamics and found that two-dimensional radial situations cannot be reducible to Fourier law with the effective thermal conductivity. As for experiments, Liu & Asheghi [17,18] obtained the in-plane effective thermal conductivity of silicon films by introducing a steady-state uniform internal heat source and measuring the average temperature increase.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have focused on the reduction of in-plane effective thermal conductivity in the nanofilms [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and tried to characterize the thermal transport with phonon-boundary scattering by the modification of effective thermal conductivity [24][25][26]. Analytical effective thermal conductivity models were derived based on the steady-state phonon Boltzmann transport equation [9,10], extended irreversible thermodynamics [11] and phonon hydrodynamics [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior shown in Figure 3 is anomalous, since the temperature profile in the layer is not everywhere decreasing with the radial distance, as it would be expected from the classical Fourier law [23]. Since in the present problem, the only heat source is the hot device at r * ≡ 1, that behavior (arising from the model Equation (7)) points out that in the circular layer, there are regions wherein the heat is flowing from colder points to hotter ones.…”
Section: Thermodynamic Compatibilitymentioning
confidence: 90%
“…The presence of that hump (see Figure 3) suggests that there are some areas wherein the heat flows from colder points to the hotter ones. This result completely disregards that arising from the classical Fourier law [23], which predicts that heat can only flow from the hotter zones to the colder ones. However, to check whether the theoretical predictions arising from Equation (2) are physically admissible, or not, we have analyzed the temperature hump in view of the second law of thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation